Market finance as a spare tyre? Corporate investment and access to bank credit in Europe - Laurent Maurin; Malin Andersson; Desislava Rusinova (European Investment Bank (EIB), 2021)
We estimate a FAVAR with Bayesian techniques in order to investigate the impact of loan supply conditions on euro area corporate investment and its financing structure. We identify shocks to overall demand and loan supply with sign and impact restrictions. Although tightened financial conditions have adversely impacted corporate investment during and after the sovereign debt crisis, the resulting impediments in loan supply, illustrated by lower loan volumes and higher spreads, have been partly alleviated by strengthened corporate debt issuance. We show that (1) part of the protracted increase in debt to loan ratio since the crisis reflects bottlenecks in the provision of bank credit and (2) the tightened loan supply has been more adverse for small corporations with limited market access. Overall, our analysis of macro-financial developments suggests the need for policy actions to deepen the European corporate debt market and enhance market access for smaller corporates.
Keywords: E22; E66; G21; 330; financing structure; small and medium size corporates; size spread; corporate debt issuance; FAVAR model